Driving Factors of Medical Students' Engagement in Rural Revitalization: Insights from the Youth Red Dream Journey - Feng, Hanchao; Wei, Yi; Keat, Ooi Boon; Musah, Adiza Alhassan (Journal of Neonatal Surgery, 2025)
This study investigates whether social responsibility, social capital, entrepreneurial self-efficacy, and achievement motivation influence medical students' engagement in rural revitalization projects, specifically within the framework of the "Youth Red Dream Journey" initiative. Rural revitalization is a core aspect of China's national development strategy, aiming to mitigate healthcare disparities in underserved regions, where medical students are positioned to play a pivotal role. Using data collected through a structured survey and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM), this research assesses the predictive strength of these four psychological and contextual factors. The findings reveal that all four variables exert significant positive effects on project engagement, with entrepreneurial self-efficacy demonstrating the strongest impact. These results underscore the need to integrate entrepreneurship, civic values, and social network cultivation into medical education. This study offers actionable insights for educators and policymakers seeking to encourage rural healthcare participation and ensure the sustainable success of revitalization initiatives.